Cultural and Environmental Dynamics in Social Transformation: The River-to-Land Transition in Central Kalimantan, Indonesia - Sriyana Sriyana (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2025)
This study investigates the socio-cultural transformation of the Bakumpai community in Tumbang Samba, Central Kalimantan, driven by a major shift from river-based to land-based life. Traditionally reliant on riverine systems for livelihood, mobility, and identity, the community has undergone fundamental changes due to infrastructure development and the prohibition of illegal logging and mining. The objective of this research is to explore the dynamics of social change in this context, particularly how internal resilience and external pressures intersect to shape new social patterns. Employing a qualitative research design, the study used interviews, observations, and applied grounded theory through open coding procedures to generate conceptual categories. The findings reveal five key domains of transformation: spatial reconfiguration, occupational transition, technological integration, reorganization of social relations, and cultural reinterpretation. These shifts mark a profound redefinition of identity, economy, and interaction—from water-bound collectivism to land-based functional differentiation. The adoption of mobile technology, the relocation of settlements and trade centers, and the diversification of economic activities signify a move toward a digitally connected land society. In conclusion, the study offers a substantive theory of transition from river dependency to networked land adaptation, demonstrating how communities co-produce change by blending traditional values with modern modalities in response to policy, infrastructure, and ecological restructuring.